The Comparison of Self-Perception of the Use of Learning Strategies in Spanish and Lithuanian Secondary Students When Learning Science - Ortega-Torres, Enric; Drąsutis, Sigitas; Burbaitė, Renata (Pedagogika, 2023)
Improving students‘ learning strategies is important for them in order to learn successfully. This article compares the self-perception of the use of learning strategies in Spanish and Lithuanian secondary schools students when learning science and analyse the students understanding of these strategies to determine the sociocultural environment influence on this perception. Results emphasize the need to include support actions to improve the management of strategies in secondary school.